Penggunaan Dokumen Elektronik sebagai Alat Bukti dalam Tindak Pidana Prostitusi Di Media Sosial: The Use of Electronic Documents as Evidence in Prostitution Crimes on Social Media - Farid Septyan Fathoni (CLEAR: Criminal Law Review, 2025)
This research has two objectives. First, to describe and explain the legal regulations contained in Indonesian legislation regarding electronic evidence that is closely related to the criminal act of online prostitution on social media. Second, to analyze the procedures and processes used in court proceedings in relation to the use of electronic evidence in the form of electronic documents in criminal acts of prostitution on social media. This study uses normative juridical research with statutory and conceptual approaches. The technique of collecting legal materials is carried out through document or literature studies of existing legal materials. The results of this study indicate, first, that electronic evidence has been specifically regulated in the provisions regarding electronic information. As electronic evidence, it can take the form of information, important documents, as well as other data that fall within the electronic scope. The legality of electronic evidence is not only contained in the ITE Law but is also accommodated in regulations outside the law. The difference lies only in the position of the evidence, whether it stands alone or serves as supporting evidence. Second, that the settlement of criminal cases of prostitution on social media, in terms of proof, refers to the provisions of the ITE Law as the basis for the use of electronic evidence. However, the overall process of criminal proceedings continues to use the Criminal Procedure Code (KUHAP) as the foundation, from examination up to the resolution process at the subsequent stages. Penelitian ini mempunyai tujuan, pertama, Untuk mendeskripsikan dan menguraikan bagaimana aturan hukum yang ada dalam perundang-undangan di Indonesia mengenai alat bukti elektronik yang erat kaitannya dengan tindak pidana prostitusi Online di media sosial. Kedua, Untuk menganalisis alur dan proses yang digunakan dalam persidangan kaitannya dengan pembuktian menggunakan alat bukti elektronik yang berupa dokumen elektronik pada tindak pidana prostitusi di media sosial. Penelitian ini menggunakan penelitian yuridis normatif, dengan pendekatan undang-undang dan pendekatan konseptual. Teknik pengumpulan bahan hukum yang digunakan adalah studi dokumen atau kepustakaan terhadap bahan hukum yang ada. Hasil penelitian menunjukkan bahwa, pertama, Bahwa secara khusus alat bukti elektronik sudah diatur dalam ketentuan peraturan tentang informasi elektronik, sebagaimana bukti elektronik bahwasanya alat bukti elektronik ini bisa berupa suatu informasi baik dokumen informasi penting dan juga informasi lainya yang masih dalam lingkup elektronik. Serta legalitas alat bukti berupa elektronik tidak hanya terdapat dalam UU ITE saja, namun ketentuan di luar UU tersebut juga ikut serta mengakomodir alat bukti berupa elektronik tersebut, namun yang membedakan hanya pada penempatan sebagai bukti yang berdiri sendiri atau bukti sebagai petunjuk. Kedua, Bahwa penyelesaian perkara tindak pidana prostitusi pada media sosial, proses pembuktiannya mengacu pada ketentuan UU ITE sebagai suatu dasar penggunaan alat bukti elektronik. Namun, proses keseluruhan acara pidananya tetap menggunakan dasar KUHAP dalam pemeriksaan hingga proses upaya penyelesaian di tingkat selanjutnya.